Priming of microglia with IFN‐γ impairs adult hippocampal neurogenesis and leads to depression‐like behaviors and cognitive defects. Issue 12 (11th July 2020) - Zhang, Jinqiang; He, Hui; Qiao, Yan; Zhou, Tao; He, Haili; Yi, Saini; Zhang, Lijuan; Mo, Li; Li, Yahui; Jiang, Weike; You, Zili
Abstract: Neuroinflammation driven by interferon‐gamma (IFN‐γ) and microglial activation has been linked to neurological disease. However, the effects of IFN‐γ‐activated microglia on hippocampal neurogenesis and behavior are unclear. In the present study, IFN‐γ was administered to mice via intracerebroventricular injection. Mice received intraperitoneal injection of ruxolitinib to inhibit the JAK/STAT1 pathway or injection of minocycline to inhibit microglial activation. During a 7‐day period, mice were assessed for depressive‐like behaviors and cognitive impairment based on a series of behavioral analyses. Effects of the activated microglia on neural stem/precursor cells (NSPCs) were examined, as was pro‐inflammatory cytokine expression by activated microglia. We showed that IFN‐γ‐injected animals showed long‐term adult hippocampal neurogenesis reduction, behavior despair, anhedonia, and cognitive impairment. Chronic activation with IFN‐γ induces reactive phenotypes in microglia associated with morphological changes, population expansion, MHC II and CD68 up‐regulation, and pro‐inflammatory cytokine (IL‐1β, TNF‐α, IL‐6) and nitric oxide (NO) release. Microglia isolated from the hippocampus of IFN‐γ‐injected mice suppressed NSPCs proliferation and stimulated apoptosis of immature neurons. Inhibiting of the JAK/STAT1 pathway in IFN‐γ‐injected animals to block microglial activation suppressed microglia‐mediated neuroinflammation and neurogenic injury, and alleviated depressive‐like behaviors and cognitive impairment. Collectively, these findings suggested that priming of microglia with IFN‐γ impairs adult hippocampal neurogenesis and leads to depression‐like behaviors and cognitive defects. Targeting microglia by modulating levels of IFN‐γ the brain may be a therapeutic strategy for neurodegenerative diseases and psychiatric disorders. Main Points: IFN‐γ induces microglial activation through the JAK/STAT pathway. Priming of microglia with IFN‐γ impairs immature neurons and adult hippocampal neurogenesis. Priming of microglia with IFN‐γ leads to depression‐like behaviors and cognitive defects.